(untitled) (Bangladesh Journal of Anatomy, 2011)
Ultimately, every cell in the human body can be traced back to a fertilized egg that came into existence from the union of ovum and sperm. But the body is made up of over 200 different types of cells, not just one. All of these cell types come from a pool of cells in the early embryo, called stem cells. DOI: http://dx.doi.org/10.3329/bja.v9i1.8138 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 1-4